The EMT transcription factor ZEB1 blocks osteoblastic differentiation in bone development and osteosarcoma. Issue 2 (6th May 2021) - Ruh, Manuel; Stemmler, Marc P; Frisch, Isabell; Fuchs, Kathrin; van Roey, Ruthger; Kleemann, Julia; Roas, Maike; Schuhwerk, Harald; Eccles, Rebecca L; Agaimy, Abbas; Baumhoer, Daniel; Berx, Geert; et al.
Abstract: Osteosarcoma is an often‐fatal mesenchyme‐derived malignancy in children and young adults. Overexpression of EMT‐transcription factors (EMT‐TFs) has been associated with poor clinical outcome. Here, we demonstrated that the EMT‐TF ZEB1 is able to block osteoblastic differentiation in normal bone development as well as in osteosarcoma cells. Consequently, overexpression of ZEB1 in osteosarcoma characterizes poorly differentiated, highly metastatic subgroups and its depletion induces differentiation of osteosarcoma cells. Overexpression of ZEB1 in osteosarcoma is frequently associated with silencing of the imprinted DLK‐DIO3 locus, which encodes for microRNAs targeting ZEB1. Epigenetic reactivation of this locus in osteosarcoma cells reduces ZEB1 expression, induces differentiation, and sensitizes to standard treatment, thus indicating therapeutic options for ZEB1‐driven osteosarcomas. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.